Kemandirian Usaha Pembudidaya Ikan dalam Proyek Pembinaan Peningkatan Pendapatan Petani-Nelayan Kecil (P4K) di Desa Muktisari, Kecamatan Cipaku, Kabupaten Ciamis, Jawa Barat - Desy Purwayanti; Anna Fatchiya; Istiqlaliyah Muflikhati (Buletin Ekonomi Perikanan, 2004)
Self-reliance is an ability to choose various choices to achieve a better quality of life. The self-reliance can be grown by counselling, that is an education process to people behaviour. One of government program conducted counselling activity in its target attainment is Rural Income Generation Project (RIGP), or in Indonesia called Pembinaan Peningkatan Pendapatan Petani-Nelayan Kecila (P4K) project. This project aims to empower the small fishermen and farmers, including the fish farmer, in order to increase their ability to be free from poorness, develop their self-reliance and participation in decision making and rationally cultivation. The aim of the research are: 1) process of P4K project 2) counselling process to fish farmer 3) fisheries cultivation 4) fish farmer characteristic 5) the self-reliance level of fish farmer; and also 6) relation among fISh farmer characteristic with their autonomous level. Result of this research indicate that project in Muktisari Village started by the year 1979 and is still be executed for cooperation among Unit Penyuluh Pertanian(UPP), Bank Rakyat Indonesia ( BRI) and P4K participators. Target attainment of P4K project done through counselling and credit loan gift. Counselling process take place good enough with suitable enough frequency, method and items and also the competence extension agent. Fish and shrimp cultivation in Muktisari Village are still managed traditionally. Internal characteristics consist of age, formal education levels, sum of family member, counselling motivation, cultivating experience, cosmopolitan level, social status, counselling perception, cultivation income andsertification of ownershif. Eksternal characteristic consisted of cultivation facilities support. group dynamics, institute support, counselling performance and sum of loan. The fish farmer characteristic in Muktisar Village are relativelly uniform. Independence level of fish farmer in this research location is at a medium level. there is a medium ability in chosen commodity type, accessing cultivation facilities and comprehend market, low ability in determine price and look for information. and have been had high ability in work along. fish cultivation technical and -credit payment. Internal characteristic that has signifficant effect to fish farmer independence level are counselling motivation. cultivating experience. counselling perception, earnings. ownership of fix resource, group dynamics. counselling performance and sum of loan.